Persistently Transmitted Viruses Restrict the Transmission of Other Viruses by Affecting Their Vectors - Chen, Gong; Su, Qi; Shi, Xiaobin; Pan, Huipeng; Jiao, Xiaoguo; Zhang, Youjun (Frontiers in Physiology, 2018)
Diverse pathogens, plant hosts, insect vectors, and non-vector herbivores coexist and interact in natural systems. This is the case of the insect Bemisia tabaci Q and Frankliniella occidentalis and the pathogens Tomato yellow leaf curl virus (TYLCV), and Tomato spotted wilt virus (TSWV) that can co-occur on the same plant. In addition, both TYLCV and TSWV are persistently transmitted in this insect species. However, the TSWV reduces the fitness of B. tabaci Q, therefore we investigated whether TSWV affects the transmission of TYLCV to tomato. Both TYLCV and TSWV are persistently transmitted. Although B. tabaci Q cannot transmit TSWV, we found that this insect species is able to acquire and retain this virus serotype, indicating that the effects of TSWV on TYLCV transmission in the current study result from effects on the vector. The acquisition, retention, and transmission of TYLCV by B. tabaci Q were reduced when the insect vector contained TSWV. Additionally, the TYLCV acquisition and transmission by B. tabaci Q were reduced when the host plant was inoculated with TSWV before TYLCV or simultaneously with TYLCV. We also found that F. occidentalis fecundity and transmission of TSWV were reduced when F. occidentalis contained TYLCV. Our findings are consistent with the hypothesis that persistently transmitted viruses can restrict the transmission of other viruses by affecting their insect vectors.